Basic Education: Learning Difficulty, the teacher's perception and his pedagogical action with children in the final grades of kindergarten and early elementary school (Research, Society and Development, 2019)
From a bibliographic and investigative nature, this article proposes to present concepts about the specific learning difficulties, its relation with the psychomotricity in the initial school phase, and the teacher's performance in face of this fact. The general objective is to identify and analyze how the teacher, as a mediator and intervener of learning and difficulties in this process, can intercede for the child to build their knowledge, since in the daily school, there is a significant growing number of children who cannot learn. . The methodology used is structured in documentary and bibliographic research; The objectives are characterized as descriptive from field research analysis, through data collection; quanti-qualitative research. For this, we developed an exploratory research, based on the analysis of official documents and articles that discuss this process. From this research, it was possible to detect the urgent need to propose partnerships with professionals from other areas such as psychopedagogues, social workers, psychologists and psychiatrists, and to better train the faculty, specializing it, since they can together minimize the difficulties of each child, offer new strategies that lead them to meaningful learning, developing skills and competences, respecting individuality and the same opportunities.